Jonathan I. Israel, The Enlightenment that Failed: Ideas, Revolution and Democratic Defeat, 1748–1830 - Sfoini, Alexandra (The Historical Review/La Revue Historique, 2022)
Review of: Jonathan I. Israel, The Enlightenment that Failed : Ide as, Revolution and Dem ocr atic Defe at, 1748–1830, Oxford: Oxford University Press, 2019, ix + 1070 pages.